Answer:
(- 2, 5 )
Step-by-step explanation:
Given the 2 equations
3x + 4y = 14 → (1)
x = 2y - 12 → (2)
Substitute x = 2y - 12 into (1)
3(2y - 12) + 4y = 14 ← distribute and simplify left side
6y - 36 + 4y = 14
10y - 36 = 14 ( add 36 to both sides )
10y = 50 ( divide both sides by 10 )
y = 5
Substitute y = 5 into (2) for corresponding value of x
x = 2(5) - 12 = 10 - 12 = - 2
Solution is (- 2, 5 )
The answer would be
7/11=0.6363636364
Answer:
A translation by 1 units to the right and 3 units down.
Step-by-step explanation:
Answer:
x = 15
Step-by-step explanation:
We want to solve for x in 3*(2x + 5) = 3x + 4x
First simplify.
3*(2x + 5) = 7x
Next, distribute the 3.
3*2x + 3*5 = 7x
6x + 15 = 7x
15 = 7x - 6x
15 = x